Investigating reading challenges experienced by grade 10 learners in sepedi home language classrooms at Mphahlele Circuit - Mello, Seome Robert (My University, 2023)
This research is about the reading challenges faced by rural Grade 10 learners in the Mphahlele sub-district, Southern Capricorn sub-district, Limpopo province of South Africa. The challenges of reading more in the home language are global. The study was conducted with a focus on two high schools, with a focus on grade 10 learners. The researcher used the interview and observation method for the learners after reading the novel selected for grade 10. It was revealed that most teachers and learners agree that there are challenges in reading Sepedi literature. It was revealed that reading challenges are caused by the following problems lack of library, lack of education for parents of learners, lack of skills in teaching reading by teachers, lack of learning aids for learners such as books, and the need for textbooks to teach reading. The researcher recommended that the National Education Department should build libraries and facilities in rural schools and their villages. Schools should have policies that involve parents in their children’s education. The Department of Education should recruit qualified teachers to teach Sepedi Home Language, equip schools with textbooks for learners to improve their reading skills. Also, the DBE should put in place guidelines and workshops to guide teachers on best practices for teaching learners to read well.
Thesis (M. Language Education (Sepedi)) -- University of Limpopo, 2023
Keywords: Global; Library; Textbooks and villages; Northern Sotho language; High school students -- Books and reading; Reading (Secondary) -- Ability testing